2018
DOI: 10.2147/imcrj.s163612
|View full text |Cite
|
Sign up to set email alerts
|

First-in-man intravenous implantation of stromal vascular fraction in psoriasis: a case study

Abstract: BackgroundStromal vascular fraction (SVF) is a mixture of adipose-derived stem cells/mesenchymal stem cells, endothelial/progenitors, pericytes, fibroblasts, and other cells obtained from fat tissue. A small sample of fat or adipose tissue can be obtained under local anesthesia using a cannula. After an enzymatic digestion and centrifugation, the adipocytes (fat cells) are removed to obtain an SVF. Here, we describe the rationale and, to our knowledge, the first clinical implementation of SVF intravenously in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…Nonetheless, as stromal vascular fraction isolation may be a more suitable approach for specific procedures such as intravenous delivery, alternative methods for enzymatic optimization are needed to improve and maximize the stromal vascular fraction cell yield. 34,35…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, as stromal vascular fraction isolation may be a more suitable approach for specific procedures such as intravenous delivery, alternative methods for enzymatic optimization are needed to improve and maximize the stromal vascular fraction cell yield. 34,35…”
Section: Discussionmentioning
confidence: 99%
“…In a case study published in 2018, injection of a MSCcontaining cell preparation obtained from adipose tissue could significantly improve the condition. The mechanisms that are involved, particularly, whether and how these cells activate immune system associated growth factors and cytokines to support wound healing and reduce inflammation, are not well-understood (Comella et al 2018).…”
Section: Skin Defectsmentioning
confidence: 99%
“…Lee et al [11] reported that human umbilical cord blood-derived mesenchymal stem cells (hUCB-MSCs) ameliorate psoriasis-like skin inflammation in mice and have regulatory effects on immune cells including CD4 + T cells and dendritic cells. The first case study on intravenous infusion of SVF into psoriasis patient demonstrated a significant decrease in symptoms with a noticeable difference in skin appearance, psoriasis area, and severity index (PASI) score reduction (from 50.4 to 0.3) [12]. Chen et al .…”
Section: Introductionmentioning
confidence: 99%